(3TQM GdJPcQI GdfUjQjI (B( (3aj Yde GdgjFI (B)s - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s ((3CMeO Hf cGQi GdNhGLg Hf ShfOc Hf EdjGS s)
(3ChdgG (B:s
(3JHGQc GdPi LYd ai GdSeGA HQhLkG hHYO , aEf Yde GdgjFI eQbGI efUhHg Edi eYGQL GdSehGJ GdYdi aCQOJ Cf CTQMg TQMkG eJhSWkG Hjf WQai ENdGd hEedGd s
(3BNQgG (B:s
(3gPG efJgi GdCHYGO GdeYdheI GdebGOjQ hCeG HYO eMOH Gdadc GdCYXe adGjYdeg EdG Gddg hdfNJe GdcJGH gGgfG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B281 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B391s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs